Eco-innovation and green start-ups: An evidence review - Blundel, R; Hampton, S (Enterprise Research Centre, 2021)
This paper examines ‘green’ start-up ventures and other forms of eco-innovation in which SMEs play an active role1 . It reviews recent evidence on entrepreneurial and innovative initiatives that address specific environmental challenges, including the Climate Emergency. A companion report (ERC SOTA Review no. 51, July 2021), focuses on the closely related issue of improving environmental performance in the general SME population.